(untitled) (Muitas Vozes, 2021)
The minimalist program proposes a model of language evolution and a comparative, interdisciplinary and empirical research program for the issue. The conception that language is an emerging capacity only in our species suggests that the selection and adaptation processes did not decisively influence the emergence of this characteristic. At the same time, the relevantist-oriented cognitive pragmatics has for more than thirty years developed a conception of the evolution of communicative behavior that diverges from the central postures of the minimalist program. This work aims to highlight epistemological and methodological issues that arise from the confrontation between both proposals. The primary statement defended here is that the adoption of a strongly adaptationist perspective for communication (relevant bias) and weakly adaptationist for language/recursion (minimalist), considering recursion, as well as verbal communication, emerging capacities of human cognition, it is possible since the centrality of the syntax, defended by the generative model and subtly reaffirmed in the minimalist program, is left aside in favor of a model that does not shy away from pointing out a natural explanation of communication via language.